2020
DOI: 10.1021/acs.energyfuels.0c00721
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Combustion, and Compatibility of High-Viscosity Heavy Fuel Oil Blends with a Fast Pyrolysis Bio-Oil

Abstract: Properties related to the combustion, stability, and compatibility of blends composed of high-viscosity heavy fuel oil (HFO) and highly acidic pyrolysis bio-oil were determined to assess the utility of bio-oil as a marine fuel. The addition of bio-oil was shown to be fully stable with HFO at blend levels up to 50 mass % for up to 2 weeks. Bio-oil concentrations as low as 5 mass % significantly reduced the viscosity of HFO at 25 and 50 °C. Aging studies at 50 and 90 °C showed that the HFO inhibited the polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…These pathways utilize HTL, fast pyrolysis, and catalytic fast pyrolysis as their conversion routes, producing either biocrude, bio-oil, or pyrolysis-oil intermediates that are then upgraded to distillate fuels using a combination of deoxygenation and hydrogenation upgrading techniques. Note that pyrolysis bio-oils and HTL biocrude derived from various feedstocks and without upgrading can be blended with HFO for marine shipping (Kass et al 2020). The upgraded diesel-range renewable diesel can be used as marine diesel.…”
Section: Product Distributionmentioning
confidence: 99%
“…These pathways utilize HTL, fast pyrolysis, and catalytic fast pyrolysis as their conversion routes, producing either biocrude, bio-oil, or pyrolysis-oil intermediates that are then upgraded to distillate fuels using a combination of deoxygenation and hydrogenation upgrading techniques. Note that pyrolysis bio-oils and HTL biocrude derived from various feedstocks and without upgrading can be blended with HFO for marine shipping (Kass et al 2020). The upgraded diesel-range renewable diesel can be used as marine diesel.…”
Section: Product Distributionmentioning
confidence: 99%
“…Other properties of FPBO to consider are its acidity and its tendency to polymerize. The high acidity (pH 2-3) of FPBO may lead to corrosion in metal and elastomeric materials of the fuel supply and injection system (Kass et al, 2015;Kass et al, 2020). Its tendency to polymerize at elevated temperatures may lead to nozzle clogging and coking (Broumand et al, 2020;Wang and Ben, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fuel blending, introduced previously for various purposes, was employed for bio-oil and heavy fuel oil (HFO, a fossil fuel) to reduce the organic acid and pollutant concentrations. , Studies have reported a decrease in acidity but an increase in sulfur content in blended fuels by lowering the content of HAHM bio-oil. In addition, 2.25Cr-1Mo steel, that readily corroded in raw HAHM bio-oil, was compatible with the blend of HFO with 8 or 19 wt % bio-oil (based on the calculated corrosion rate being lower than 0.01 mm per year).…”
Section: Introductionmentioning
confidence: 99%